Desain Antar Muka Sistem e-Learning Berbasis Web - Rusydi Umar; Anton Yudhana; Ockhy Jey Fhiter Wassalam (Program Studi Sistem Informasi, 2018)
Computer-based learning is now widely used in various schools both high school and college. The use of such computers can use of computers as aids in teaching and learning process. Along with advances in science and technology the teaching and learning process have demanded not only indoors in the form of face-to-face, but people can learn anytime and anywhere. One of the models that used for this purpose is e-learning based learning model. But to use the model must be available media. With e-learning system to study online courses. Through this system, students can more easily access course syllables, course modules, assignments and many other information reinforced by lecturers in the e-learning system so students can access them easily, when and wherever. All announcements of syllabus, module, task and announcement in lecturer by lecturer of e-learning system. With these systems, will form learning between faculty and students in addition to face to face in the lecture hall. With such interaction, it is sure to enrich the learning system and improve the quality of education. Which have been in demand and delivery according to the learning needs. Results and implementation show the system works well.Keywords: E-Learning system, web-based, learning-teaching system.